2012
DOI: 10.1039/c2cc17019a
|View full text |Cite
|
Sign up to set email alerts
|

Cascade reactions in crystals through cation–π-controlled reorientation on exposure to HCl gas

Abstract: Exposure of 4-azachalcones to HCl gas produced the corresponding HCl salts with a head-to-tail stacked alignment, irradiation of which produced the corresponding syn-HT dimers with high regio- and stereoselectivities, thus showing the effectiveness of the cascade process in crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Recent studies established 16 stilbazoles and 4-azachalcone, 1-aryl-4-pyridylbutadiene photodimerized to a single anti head-tail dimer in the solid state in the presence of HCl–H 2 O (Scheme ). The importance of water in this process became evident when dry HCl instead of aqueous HCl was used to protonate the stilbazoles. Examination of the packing arrangements of two stilbazolium salts shown in Figure revealed that hydrogen bonding between N–H---O and N–H---Cl – controlled the packing.…”
Section: Organic Crystals As a Supramolecular Assemblymentioning
confidence: 99%
“…Recent studies established 16 stilbazoles and 4-azachalcone, 1-aryl-4-pyridylbutadiene photodimerized to a single anti head-tail dimer in the solid state in the presence of HCl–H 2 O (Scheme ). The importance of water in this process became evident when dry HCl instead of aqueous HCl was used to protonate the stilbazoles. Examination of the packing arrangements of two stilbazolium salts shown in Figure revealed that hydrogen bonding between N–H---O and N–H---Cl – controlled the packing.…”
Section: Organic Crystals As a Supramolecular Assemblymentioning
confidence: 99%
“…Irradiation of the obtained HCl salt afforded the synHT dimers in high regio-and stereoselectivities (Scheme 126). 344 Figure 22 shows photomicrographs of a single crystal of 486 before and after exposure to HCl gas. After exposure for 10 min, unevenness and cracking were observed and the initial transparency was almost lost.…”
Section: Photodimerization In Solutionmentioning
confidence: 99%
“…Leider können die exakten supramolekularen Verhältnisse nicht aus den aktuellen Daten abgeleitet werden. Erstaunlicherweise wurde eine Änderung der Kristallstruktur durch den Einfluss von gasförmiger HCl auch bei verschiedenen anderen organischen Strukturen beobachtet, beispielsweise durch Amin‐Protonierung, wobei diese Änderung ausschließlich bei gasförmiger HCl auftreten …”
Section: Figureunclassified